Farming in the heat of Climate Change - Leave no soil uncovered - Francis, Diana (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2024)
Hurricanes, droughts, and extreme floods have occurred in the Caribbean due to the impact of climate change, consequently affecting agriculture. In the Dominican Republic, the freshwater lake is "dying" due to abnormally low water levels. Additionally, many of the agricultural practices employed are no longer viable or sustainable. A proposed solution is to avoid leaving any soil uncovered and refrain from practices such as monoculture, weeding, tillage, and excessive plowing. It is suggested that, to combat excessive heat, farmers should unlearn traditional practices, focus on developing drought-resistant varieties of food crops, and consistently plant and maintain cover crops on the farm in all areas and at all times.